Index of the Project Gutenberg Works of John Fiske - Fiske, John, 1842-1901; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2019)
"Index of the Project Gutenberg Works of John Fiske" by John Fiske is a compilation of various essays, historical texts, and reflections written in the late 19th century. The work organizes a multitude of Fiske's writings, including topics such as myths, the American Revolution, and the historical impact of prominent figures and events in early American history. This collection highlights Fiske's contributions to American historical and philosophical thought. The opening of this compilation presents an index, showcasing various works by John Fiske, indicating a broad thematic exploration that covers mythology, early New England history, the American Revolution, and reflections on civil and religious liberty. Each section introduces significant essays or historical narratives, setting the stage for a detailed examination of cultural myths, historical events in America, and overarching philosophical inquiries, encapsulating Fiske's engagement with the past and its implications for contemporary thinking. This introduction effectively prepares readers for the diverse subjects and insights that will be unpacked in the subsequent chapters of Fiske's influential writings. (This is an automatically generated summary.)
Release date is 2019-02-20
Produced by David Widger
Keywords: Indexes